Alice Lakwena and the Holy Spirits War in Northern Uganda, 1985-97. - Behrend, Heike (Athens, OH : Ohio University Press, 2000)
In August 1986, Alice Auma, a young Acholi woman in northern Uganda, proclaiming herself under the orders of a Christian spirit named Lakwena, raised an army called the ""Holy Spirit Mobile Forces.""
Cover; Series Page; Title; Copyright; Dedication; Contents; Figures & Tables; Preface; Foreword; 1. The Troubles of an Anthropologist; 2. The History & Ethnogenesis of the Acholi; 3. The Crisis; 4. The War of the Holy Spirit Mobile Forces; 5. The Holy Spirit Movement as a Regional Cult; 6. The March on Kampala; 7. The History of Religions in Acholi; 8. Alice & the Spirits; 9. The Texts of the Holy Spirit Movement; 10. The War in Acholi, 1987-96; Epilogue; Bibliography; Index
Description based upon print version of record.
Added to collection customer.56279.3 - Master record variable field(s) change: 072, 600, 650
Keywords: Auma, Alice -- Teachings; Spiritualism - Uganda; Acholi (African people) -- Religion; Religion and politics -- Uganda; Spiritualism -- Uganda; BODY, MIND & SPIRIT / Spirituality / Paganism & Neo-Paganism; RELIGION / Comparative Religion; Electronic books